Synoptic-Thermodynamic Investigation of the Dust Phenomenon in Isfahan Province (Case Study) - Leila Amini; Hosseinali Narimani; Mina Motamedi; Akram Parande Khozani (Nīvār)
AbstractOne of the results of climate change is the lack of fresh water and as a result land destruction or desertification, increase in wind erosion and the occurrence of dust storms. Although by implementing desertification operations, an attempt is made to control the destructive effects of dust storms, but identifying the causes of erosion, the temporal distribution of storms, and the location of the start zones of storms can be effective in the effectiveness of projects and reducing damages caused by storms. In this regard, this research was conducted with the aim of knowing the effective atmospheric factors in the activity of dust centers with domestic origin in Isfahan province. Knowing the existence of internal focuses and their location, the date of occurrence of local, intense and short-term dusts at the focal point was investigated. The results showed that convective conditions played a significant role in these cases and the occurrence of such internal dusts due to the timeframe of occurrence and locality requires thermodynamic information, especially cin, cape, TT, ki, ko, li and tools such as Skewet diagram. Also, due to the scale of these phenomena, companion maps do not help much and output of microscale models such as wrf, satellite imagery and if radar access is required